Analisis Perbandingan Algoritma Pencarian Jenis Tanaman Hias dengan Menggunakan Penerapan Metode Perbandingan Eksponensial - Fauziah, F; Gunaryati, Aris; Nurhayati, N; Farahdinna, Frenda; Kaeren, K (Brahmana : Jurnal Penerapan Kecerdasan Buatan, 2023)
The process of searching data manually certainly takes a long time, therefore a system is needed that can speed up the data search process, especially ornamental plant data. In this study, two algorithms were used to compare the optimal data search process according to the type of data being collected. The data used are ornamental plant data. The two algorithms used are Knuth Morris Pratt and Boyer Moore. The process is carried out by comparing text and existing patterns based on the type of character that is carried out in this test and utilizing the exponential comparison method with a value comparison of 109.13 using the Boyer Moore algorithm and 139.19 with the Knuth Morris Pratt algorithm so that the type of Boyer Moore algorithm can be known faster than Knuth Morris Pratt for text searches related to the types of ornamental plants in the trial in this study.